If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21a + 11 = 10a Reorder the terms: 11 + 21a = 10a Solving 11 + 21a = 10a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-10a' to each side of the equation. 11 + 21a + -10a = 10a + -10a Combine like terms: 21a + -10a = 11a 11 + 11a = 10a + -10a Combine like terms: 10a + -10a = 0 11 + 11a = 0 Add '-11' to each side of the equation. 11 + -11 + 11a = 0 + -11 Combine like terms: 11 + -11 = 0 0 + 11a = 0 + -11 11a = 0 + -11 Combine like terms: 0 + -11 = -11 11a = -11 Divide each side by '11'. a = -1 Simplifying a = -1
| -9(x+5)=6-8x | | 3^2/3^6 | | 13x+7(-3y-1)=-63 | | w=1500-150t | | 2b-3.4=-17.4 | | 450000+22000x=0 | | 7/2x+8=x+10 | | 3x^3(7x^2-2x+7)= | | 8x^2+16x+9=3 | | 78=-2(m+2)+m | | 6-4(3x-1)=-14 | | 1/(z-6)(z+4) | | 50y+8=17 | | 81=k/3 | | 18(t-5)+36=7(3t+5)-10 | | -2x+9-8x=89 | | 36-2+6= | | 7+6x=3x+31 | | 5x-4=3x-22 | | (8-x)/x=3/2 | | 1/2x-3=2x | | x+6y=21 | | 9n-5=18n+6 | | 3+3=6a-3 | | x(6x+13)=33 | | x-8y=-35 | | x^2-6x=-49 | | 6+8+2=2+8+6 | | (2cos(x))(sin(x))-sin(x)=0 | | 5b+6+58=180 | | (3+2)(3+2)= | | 10c^2-17c+6=0 |